Model of Productive Behavior of Public Elementary School Principals in Surabaya - Hardaningtyas, Dwi; Handoko, Rudy; Kusbandrijo, Bambang (Green Publisher Indonesia, 2023)
This study aims to analyze the Productive Behavior Model of Public Elementary School Principals in Surabaya in terms of Psychological Capital and Organizational Culture with Public Service Motivation as a mediator. The approach used is a quantitative approach. Respondents in this study were 211 principals of public elementary schools in Surabaya. The data collection tool used is a questionnaire with a Likert scale. The data obtained were then analyzed using the SmartPLS 3.0 program. Testing the hypothesis with the PLS approach is carried out in two stages, namely testing the outer model and the inner model. The outer model test is carried out to prove the validity and reliability of all indicators for each variable. The inner model test is used to test the influence between variables according to the hypotheses previously set. The results showed (1) Psychological Capital has a direct and significant effect on productive behavior, (2) Psychological Capital has a direct and significant effect on Public Service Motivation, (3) Organizational Culture has a direct and significant effect on productive behavior, (4) Organizational Culture has a direct effect and significant to Public Service Motivation, (5) Public Service Motivation has a direct and significant effect on productive behavior, (6) Psychological Capital has an indirect effect on productive behavior through Public Service Motivation as a mediator.